2023
DOI: 10.1177/17479541231218518
|View full text |Cite
|
Sign up to set email alerts
|

Managing concussion in the real world: Stakeholder perspectives of New Zealand Rugby's concussion management pathway

Danielle Margaret Salmon,
Simon Walters,
James Brown
et al.

Abstract: The potential adverse consequences associated with poor concussion management highlights the need to improve the translation of concussion guidelines into consistent use in real-world sport settings. To facilitate this process, New Zealand Rugby developed a community concussion management pathway to support concussion recognition, diagnosis, and management. This study adopted a pragmatic, descriptive qualitative approach to explore key stakeholders’ perceptions of the concussion management pathway, with the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Concussion management initiatives like the Blue Card presume those involved will work together for the benefit of the athlete ( 44 ). Study participants indicated that concussion management initiatives like the Blue Card assume, and in fact demand, a high degree of trust, respect, and cooperation among those responsible for implementation.…”
Section: Resultsmentioning
confidence: 99%
“…Concussion management initiatives like the Blue Card presume those involved will work together for the benefit of the athlete ( 44 ). Study participants indicated that concussion management initiatives like the Blue Card assume, and in fact demand, a high degree of trust, respect, and cooperation among those responsible for implementation.…”
Section: Resultsmentioning
confidence: 99%